The Narrative Art of Contemplator: An Analysis on Milan Kunderaâ€™s Works - Feng, Ma (Bina Nusantara University, 2009)
Article presented a narrative theoretical analysis on Milan Kunderaâ€™s works. Its emphasis point lied on the unity of the theory and the practical explanation to the text. Kunderaâ€™s works joined the unique ponder art and the narrative artistic together, which had led to the work a possible implication that would be much richer. Based on a macroscopic angle, this article used the relative theory, including theories on classic and latter classic narrates study. Then, based on the microscopic angle, this article mainly utilized the narrative theory about â€œthe interventionâ€ as well as the acceptable aesthetic theory. Whatâ€™s more, the article did not only carry on a careful narrative analysis on Kunderaâ€™s creation, but also discussed the profound effect with which the narration brought. This article offered some careful and profound discussions respectively on the narratorâ€™s and readerâ€™s intervenes. The narrator intervenes stressed that the narratorâ€™s â€œnarration person, narration method and the narration identityâ€ in the work, and discussed the narrator â€œweâ€, illusion narration, parenthesis replenishment narration as well as the Polyphony and reliability which were brought by the narration method and narratorâ€™s identity. The reader intervene stressed the readerâ€™s strategy during the connoisseurship and the acceptance process, and also evaluated readerâ€™s identity during the reading process, and concernedÂ about the lost readers in the â€œgarden paths phenomenon and jungle for explanationâ€.Â Â